2011
DOI: 10.1111/j.1528-1167.2011.03268.x
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional relation between schizophrenia and epilepsy: A population-based retrospective cohort study

Abstract: SUMMARYPurpose: Schizophrenia and epilepsy may share a mutual susceptibility. This study examined the bidirectional relation between the two disorders. Methods: We used claims data obtained from the Taiwan National Health Insurance database to conduct retrospective cohort analyses. Analysis 1 compared 5,195 patients with incident schizophrenia diagnosed in 1999-2008 with 20,776 controls without the disease randomly selected during the same period, frequency matched with sex and age. Analysis 2 comprised a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 41 publications
4
66
0
6
Order By: Relevance
“…Yet, population-based studies of primary psychiatric disorders have established that not only are PWE more likely to develop these comorbid conditions than the general population, but have also suggested that patients with "primary" psychiatric disorders are at higher risk of developing epilepsy [1][2][3][4][5][6][7]. For example, in the first study, conducted in Sweden, depressive disorders were seven times more common among patients with new-onset epilepsy, preceding the seizure disorder, than among age-and sex-matched controls [1].…”
Section: Epidemiologic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, population-based studies of primary psychiatric disorders have established that not only are PWE more likely to develop these comorbid conditions than the general population, but have also suggested that patients with "primary" psychiatric disorders are at higher risk of developing epilepsy [1][2][3][4][5][6][7]. For example, in the first study, conducted in Sweden, depressive disorders were seven times more common among patients with new-onset epilepsy, preceding the seizure disorder, than among age-and sex-matched controls [1].…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…Of note, the OR among depressed patients was higher for idiopathic or cryptogenic seizure disorders (3.9, 95 % CI 2.4-6.1) than for symptomatic seizures (1.5, 95 % CI 0.8-2.6). Likewise, in a population based-study conducted in Taiwan, patients with schizophrenia had a 6-fold higher risk of developing epilepsy than controls [7].…”
Section: Epidemiologic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that a large number of candidate CNVs are not disease-specific but are involved in the expression of different behavioural and neuropsychiatric phenotypes sharing common biological pathways, affecting glutamate and GABA neurotransmission. However, it should be stressed that the pleiotropic effect of CNVs in neuropsychiatric disorders, may be due not only to haploinsufficiency, but also to the contribution of additional genetic, epigenetic and environmental factors yet unidentified [9].…”
Section: What Are the Mechanisms Underlying These Disorders?mentioning
confidence: 99%
“…Группа ученых из Тайваньского медицинского уни-верситета [56] провела анализ базы данных Национально-го центра медицинского страхования и медицинской ста-тистики за 1998-2008 гг. Они выбрали 5195 больных ши-зофренией (по сравнению с 20 776 -без шизофрении) и 11 527 -с эпилепсией (по сравнению с 46 032 -без эпи-лепсии).…”
unclassified